Beyond Balassa and Samuelson: Real Convergence, Capital Flows, and Competitiveness in Greece - Ansgar Belke; Ulrich Haskamp; Gunther Schnabl; Holger Zemanek (Center for Economic Studies and ifo Institute (CESifo), 2015)
We scrutinize the role of capital flows for competitiveness in seven euro-area countries in the context of real convergence and crisis with a specific focus on Greece. The paper extends the seminal Balassa-Samuelson model to include international capital markets. Capital flows are assumed to be able to invert the traditional direction of transmission of real wage increases from the tradable to the non-tradable sector and to cause real wages to increase beyond productivity increases. Panel estimations for the period from 1995 to 2013 show evidence in favour of capital inflow-driven real wage increases in excess of productivity increases in Greece.
Keywords: E24; F16; F31; F32; 330; Balassa-Samuelson effect; capital inflows; exchange rate regime; inflation; Estonia; Greece; Latvia; Lithuania; Portugal; Slovenia; Slovak Republic; panel model; productivity differential; wages